Climate vulnerability and adaptation of the smallholder cocoa and coffee value chains in Liberia - Schroth, Götz; Läderach, Peter R.D.; Martínez Valle, Armando Isaac; Bunn, Christian (2015)
Liberia is one of the world’s poorest countries. Efforts to rebuild its economy after several years of internal conflict were partially set back by the 2014–5 Ebola crisis. The country’s lowland humid climate and land-use history suggest a potential to increase the production of cocoa (Theobroma cacao) and coffee (Coffea spp.) to generate income and employment for smallholder farmers, and these value chains are, therefore, the focus of projects funded by donors including the International Fund for Agricultural Development (IFAD) and the World Bank. This study analyzes the present and projected future climatic conditions of the country and compares them with conditions in other cocoa- and coffee-producing parts of Africa. Soil conditions, farming systems and supply chain characteristics are also briefly reviewed. On the basis of this information, a comprehensive strategy to reduce the vulnerability of the cocoa and coffee supply chains to climate change and ensure their future viability is proposed.